Peningkatan Kualitas dan Produktivitas Ubi Jalar melalui Implementasi Prinsip Good Agricultural Practices dalam Pelatihan Pertanian Terpadu di Desa Purwasari, Bogor - Bahroin Idris Tampubolon; Bramada Winiar Putra; Ridwan Diaguna; Raudya Zahra Maulania; Nadia Mayla Faiza; Muhammad Farhan; Choirul Anam; Daffafauzan Daffafauzan; Andira Shafa Tuffahati; Dinda Azraini; Auralia Fikri Insani; Febriana Nur Aulia; Made Naradhara Ayuko Natih; Diva Kaila Syafitri; Akbar Hermawan; Sagita Salsabila (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Purwasari Village, Dramaga District, has great potential for sweet potato cultivation, which can open up significant economic opportunities for farmers, but challenges in sustainability and improving production quality are still obstacles. One of the efforts made to overcome this is through integrated agricultural training, which focuses on improving sweet potato cultivation techniques through the IPB Innovation KKN-T program. This activity aims to help farmers understand good crop cultivation practices, Good Agriculture Practice (GAP), and increase the productivity of sweet potato cultivation. The method of implementing the activity is carried out through several stages, namely land processing, planting sweet potato seeds, training, presentation of material, giving pre-tests and post-tests related to Good Agriculture Practice (GAP), and installing 60 × 40 cm land identity signs. The results of this training show an increase in the knowledge of sweet potato farmers by 7%, as measured by the results of the pre-test and post-test, as well as an increase in farmers' participation in cultivating sweet potatoes. The implementation of the training also increased sweet potato production by 30%. This activity also collaborates with IPB's Agribusiness and Technology Park (ATP) as a partner, so that harvested sweet potato products can be further processed, marketed, and sold through the ATP distribution network. This program is expected to contribute significantly to the development of sustainable integrated agriculture, as well as improve the welfare of farmers through wider market access and added value to sweet potato products.